Clinical study on the effect of temporomandibular joint disc anchorage on surface electromyographic characteristics of the masticatory muscles - LIN Yuxiang; LI Chenxi; GONG Zhongcheng (Kouqiang hemian waike zazhi)
[Objective:] To evaluate the effect of temporomandibular joint disc anchorage (DA) on the surface electromyography (sEMG) characteristics of the masticatory muscles and its clinical outcome. [Methods:] A total of twenty-three patients with anterior disc displacement without reduction (ADDwoR) who underwent temporomandibular joint disc anchorage (DA) between December 2022 and January 2024 were collected to compare their preoperative, 3-month postoperative, and 6-month postoperative maximal interincisal opening (MIO), visual analogue scale (VAS) scores, mandibular border movement (BM) distance, and sEMG of anterior temporalis (TA) and masseter muscle (MM). [Results:] Patients' MIO increased at 6 months postoperatively compared with preoperative levels (P<0.05), BM distance did not change significantly, VAS scores during wide mouth opening and in the preauricular region decreased compared with preoperative levels (P<0.05). In unilateral DA patients, the mean amplitude of TA sEMG was higher at 6 months postoperatively than that at 3 months postoperatively (P<0.05). At 6 months postoperatively, the mean MM sEMG amplitude was elevated on the non-operative side compared with preoperative and 3-month postoperative levels, and was reduced on the operative side compared with 3-month postoperative levels. The non-operative side showed higher amplitude than the operative side both preoperative and 6 months postoperatively, and lower amplitude at 3 months postoperatively (P<0.05). In bilateral DA patients, the mean TA sEMG amplitude decreased at 3 months postoperatively compared with preoperative levels (P<0.05), and the mean MM sEMG amplitude decreased at 3 months postoperatively compared with preoperative levels, but increased and was higher than the preoperative levels at 6 months postoperatively (P<0.05). [Conclusion:] DA can reduce the pain of ADDwoR patients, improve the mandibular motor function, and make the sEMG tend to be balanced and stable, with good clinical efficacy.